(untitled) (Acta Scientiarum. Agronomy, 2011)
Due to its long production cycle, the Peruvian carrot has been cultivated on marginal land, resulting in low yields. Intercropping is an option for planting in better areas, but there is a lack of research on crop shade tolerance. This study aimed to evaluate the effect of period and intensity of artificial shading on mass partitioning and root yield on Peruvian carrot ‘Amarela de Carandaí’. The treatments were four shading intensities (18, 30 and 50% of shading with Sombrite® cover and full sun), imposed either from 30 to 120, or from 30 to 210, or from 120 to 210 days after planting (DAP), totaling 10 treatments at harvest (210 DAP), with four repetitions. Light restriction above 18% from 30–210 DAP and from 120–210 DAP reduced marketable root yield. The marketable root yield was less reduced when shading was imposed earlier (30–120 DAP) than later (120-210 DAP) on the growth cycle. Regarding light competition, Peruvian carrot should be intercropped with crops that promoted up to 50% of shading from 30-120 DAP, or up to 18% of shading from 120 to 210 or 30-120 DAP.